ISOLASI LIKOPEN DARI BUAH TOMAT (Solanum lycopersicum L) dan UJI AKTIVITAS LIKOPEN TERHADAP BAKTERI Salmonella thypi - Earlyna Sinthia Dewi; Aliefman Hakim; Lalu Rudyat Telly Savalas (Postgraduate, University of Mataram, 2019)
This research aims to know the effectiveness of lycopene antibacterial, through knowing bending zone lycopene towards salmonella thypi. This research has been success to isolate lycopene through extraction process used reflux method at 60oC temperature, using chloroform and methanol as antisolvent. Lycopene extract got 5,12 mg/100 g, analysis of functional groups by using spectroscopy Fourier Transform InfraRed (FTIR) detected C=C alkena alifatik at 1674,91 dan 1639,65 cm-1 wave length, C-H(CH3) detected at 1378,71 cm-1 wavelength, C-H (stretching) alifatikfunctional groups detected at 2853,12 cm-1 wave length, C-H alkena (stretching) detected at 2924,16 cm-1 wave length, and C-H alkena (bending) detected at 1498,86 cm-1 wave length. Inhibitory zone testing of salmonella thypi used paperdisc method with three repetitions. The mean diameter of the inhibitory zone of bacteria formed in positive control was 33,17 mm, negative control was 0 mm. Mean diameter of bacterial inhibitory zone at 3 % concentration with 3, 68 mm mean diameter and maximal Inhibitory zone at 50 % concentration with 15,12 mm mean diameter . The result of this research shown that lycopene extract has bacterial activity towards salmonella thypi Kewords: Isolation, Lycopene, Salmonella thypi, Antibacterial